Enhancing Teachers’ Competence in the Learning of Fiqih Mawaris through the Collaboration of Conventional and Modern Media At-Tashil Digital Application at Balai Diklat Keagamaan Aceh - Nurdin, Nurdin (Omega: Jurnal Fisika dan Pendidikan Fisika, 2019)
Problems in today?s learning includes the low competence of teachers in the use of media for teaching and learning. Among the weaknesses of teachers is the lack of the ability in using the media in learning ?qih mawaris. Many teachers still use conventional media such as markers, board and paper. This a?ects on the low level of students? ability on the subject of ?qih mawaris. This study aims to understand the competence of teachers in teaching and learning ?qih mawaris through the collaboration of conventional media and digital media (the application of At-Tashil) at the training center of Balai Diklat Keagamaan (BDK) Aceh. This study adopts qualitative approaches. Data were collected through interviews, the study of documents and observations, while collected data were analyzed through data reduction, presentation of data and the withdrawal of conclusion. The results show that teachers? competence on subjects of the ?qih mawaris was improved through the process of collaboration between conventional media and modern media of At-Tashil application.